RHEUMATOID ARTHRITIS: LABORATORY MODELS OF THE DISEASE - I. A. Orlovskaya; D. D. Tsyrendorzhiev; S. N. Shchelkunov (Медицинская иммунология, 2015)
The  establishment and  application of animal  models  represent effective  tools  for  research  in rheumatoid arthritis (RA) pathogenesis. Animal models that replicate various mechanisms reflecting all aspects of RA, including early RA pathology, have provided important insights into studying etiology and pathogenetic mechanisms of RA in humans. This review article was compiled in order to give an introduction to the current state of RA models.  Application of these  experimental disorders  for testing  potential therapeutic approaches will help to make better predictions for drug efficiency in human RA